Appraisal of the Physiological Response of Cakile maritima and Brassica juncea for Tolerating Lanthanum Stress - Houda Bouslimi; Nesrine Dridi; Renata Ferreira; Pedro Brito; Isabel Caçador; Saida Hidouri; Noomene Sleimi (Journal of Marine Science and Engineering, 2023)
Rare earth elements were extensively employed for many years to improve plant growth in farming. However, their effect on plant’s behavior relies on their concentration and the plant species. The impact of low doses of lanthanum (La; 1–10 µM) on plant growth, mineral uptake, and the production of secondary metabolites was assessed in two Brassicaceae species (Cakile maritime and Brassica juncea) after 14 days of La exposure. The La accumulation potential was also evaluated. Results showed that both species were able to maintain good dry biomass production under La. C. maritima plants accumulated more La than B. juncea, and a higher accumulation was noticed in the roots (in both plant species). Accordingly to La accumulation in plant tissues, nutrient absorption was affected in C. maritima shoots and roots, whereas no severe effect on nutrient contents was noticed in B. juncea. Phenolic compounds increased in the aerial and underground parts of both species; thus, the accretion was more notorious in shoots of the highest La concentrations. The studied Brassicaceae species showed an ability to survive in a La-contaminated medium. However, according to tolerance index values, C. maritima was found to be more tolerant of La than B. juncea.